The Exploratory Analysis of Urgence of Islamic Education to Develop The Personality of School-Age Children - Sarwo Edy; Jaedi Jaedi (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
This study aims to investigate the importance of implementing of Islamic education to develop the personality of school-age children. Every human being has a personality that is different from one other. The existence of this difference makes humans belong to unique creatures. This research was a qualitative approach with a type of library research. This study will analyze the importance of Islamic education for children in various pieces of literature. The results showed that the factors that affect the child's age come from the innate (inside), the environment (outside), and the maturation of his soul. Islam views every person has mental and physical potential that can elevate his dignity as caliph on this earth. Humans have soul potential which includes heart, lust, reason, and spirit. To cultivate the potential to become a good personality, the role and duties of parents have a great responsibility to foster children's mentality to be directed to the mental development of Muslim personalities.